Physiological and physical responses according to the game surface in a soccer simulation protocol - López-Fernández, J.; Sánchez-Sánchez, J.; Garcia-Unanue, J.; Felipe, J. L.; Colino, E.; Gallardo, l. (International Journal of Sports Physiology and Performance, 2018)
Purpose: Recent studies have shown that soccer players` responses are similar on natural grass (NG) and artificial turf (AT), but they did not control the mechanical properties of these surfaces. This work aimed to analyze the influence of the game surface on amateur soccer players` physical and physiological responses using a soccer simulation protocol. Methods: A total of 16 amateur players performed 3 bouts of the soccer simulation protocol on AT, and, on another day, 3 bouts on NG. The mechanical properties of both surfaces were recorded. The order of surfaces was randomly established for each participant. Physiological responses of players were assessed before and after the 6-repeated-sprints test existing at the midpoint of each bout. Fatigue (% best; % diff) and general variables (total time; best time, mean time; maximum speed) for both the repeated sprint test (RST) and the agility tests (nonlinear actions at maximum speed) incorporated into the soccer simulation protocol were also analyzed. Results: The 2 surfaces displayed different mechanical properties. Physical responses were found similar for both surfaces (P>.05) before and after the RST. There were no surface differences in sprint times or fatigue variables for the RST (P>.05). The agility test was faster on AT than on NG in bout 1 (average speed [+1.17 km/h;P=.037]; agility test cut time [-0.31 s; P=.027] and best time [-0.52 s; P=.042]). Conclusions: The differences in the mechanical properties of the 2 surfaces are not sufficient to cause differences in the physiological and physical responses of soccer players, although they may affect turns and cuts.